CULTURE AND PSYCHOLOGY OF COMMUNICATION IN PEDAGOGICAL ACTIVITY - Abdullazhonova Shakhnoza Akbarovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses the general rules of etiquette for the activities of a teacher, pedagogical tact, manners of a teacher and her role in the upbringing of the future generation. Communicative competence, purposefully improved in the process of rhetorical education, acts as an important component of the professional competence of graduates of higher education institutions in modern conditions of a dynamically developing society.